The Role of Planting Time Determination and Land Drainage Management on the Risk of Rice Crop Failure in Flood-Prone Areas in Indonesia - Salwa Aulia Novitasari; Rahmat Joko Nugroho (Westscience Press, 2026)
Rice farming in flood-prone areas of Indonesia faces persistent risks of crop failure due to climate variability, particularly excessive rainfall and prolonged inundation. Effective adaptation strategies are therefore essential to sustain rice production and farmers’ livelihoods. This study aims to analyze the role of planting time determination and land drainage management in reducing the risk of rice crop failure in flood-prone regions of Indonesia. A quantitative research approach was employed using survey data collected from 150 rice farmers. The data were obtained through a structured questionnaire measured on a five-point Likert scale and analyzed using SPSS version 25. Multiple linear regression analysis was applied to examine both partial and simultaneous effects of the independent variables on crop failure risk. The results indicate that planting time determination has a significant negative effect on the risk of rice crop failure (β = −0.381; p < 0.05), while land drainage management also shows a significant negative effect (β = −0.296; p < 0.05). Simultaneously, both variables explain 46.8% of the variation in crop failure risk. These findings highlight the importance of integrating adaptive planting decisions with effective drainage management to enhance the resilience of rice farming systems in flood-prone areas. The study provides empirical evidence to support policy interventions and agricultural extension programs aimed at improving climate-resilient rice production in Indonesia.